PENGARUH BEBAN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MODERASI ( Studi Pada Sekretariat Daerah Kabupaten Rembang ) - Moh. Nur Said, 1352020026 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to analyze the effects of workload and competence to employee performance with organizational commitment as a moderation in the Regional Secretariat of Rembang Region. The population in this study was a civil servant at the Regional Secretariat of Rembang Region, amounting to 168 people. Sampling by using the